Firms' financial performance from intellectual capital and capital structure perspectives: A comparative analysis into three industries in Malaysia / Hapsah@Kalthom S. Mohammad - S. Mohammad, Hapsah@Kalthom (Institute of Graduate Studies, UiTM, 2018)
The world's economy has changed from an industrial economy, in which economic growth was determined by the employment of physical resources, towards a knowledge-based economy in which wealth creation is associated with the development and maintenance of intangible resources particularly knowledge to create competitive advantages. The transition towards a knowledge-based economy is changing the business model and firms operating in the knowledge-based economy require interaction with their environment in order to sustain their business. Since knowledge is a source of competitive advantage, therefore, firms must employ a mechanism to identify, measure and manage it. Knowledge in firms is embedded in their employees, structural design, interaction with their environment and collectively they are referred to as intellectual capital. Due to the importance of intellectual capital capabilities as a driver of growth, more studies involving multiple industries and a model that can better reflect and measure the components of intellectual capital such as MVAIC are required. Meanwhile, capital structure decision as to how do firms choose their capital structure to finance their operations and how does the choice of capital structure financing affect the financial performance of the firm will also be examined in this study and to investigate the role of firm size in moderating the above relationships...